2020
DOI: 10.18502/acta.v57i11.3266
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior and Correlates Among Students of Tehran University of Medical Sciences

Abstract: Exercise and physical activity have well known physical and mental benefits, especially during students' life .This study was conducted to evaluate physical activity among students of Tehran University of Medical Sciences (TUMS). We have randomly recruited students of TUMS in the 2017-2018 academic year to report their routine physical activity through filling out the Persian version of the Global Physical Activity Questionnaire as well as demographic characteristics among 12 different schools. Accordingly, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Also, the intensity (i.e., vigorous or moderate) of activity in each domain and the time spent on sedentary behaviors (e.g., sitting, watching TV) are determined. The Persian version of GPAQ has been used in many national and local studies as a valid and reliable questionnaire (Esteghamati et al 2011 ; Fattahi et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Also, the intensity (i.e., vigorous or moderate) of activity in each domain and the time spent on sedentary behaviors (e.g., sitting, watching TV) are determined. The Persian version of GPAQ has been used in many national and local studies as a valid and reliable questionnaire (Esteghamati et al 2011 ; Fattahi et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Three studies revealed no statistical significance between PA and AP (18,22,24). One study concluded that PA, AP, and depression were negatively associated (20).…”
Section: Discussionmentioning
confidence: 98%
“…GPA is the most popular way to assess AP. Seven reviewed studies used GPA to measure AP among university students (12,17,1,18,19,20,21). In addition, some studies used students' raw semester average (22), marks obtained in the most recent pathology class test (23), and the average grade marks in all subjects conducted by the students (24).…”
Section: Discussionmentioning
confidence: 99%
“…Andhra Medical College in the overall (QoL) [16] , Tehran University of Medical Sciences [20] and China Medical University in the environment [2] . This variation in scores could be due to extra responsibilities imposed on males in the context of daily life.…”
Section: Discussionmentioning
confidence: 99%